DEVELOPMENT AND EVALUATION OF MICROEMULSION FORMULATIONS OF LORNOXICAM - Islam, Md. Shahidul; Uddin, Md. Irfan (Universal Journal of Pharmaceutical Research, 2023)
Background and aims: Microemulsions (ME) basically are the mixture of oil, surfactant (SA) and water, with a co surfactant (Co-SA) in different ratio. This mixture is clear and stable. The final prepared fluid possesses low viscosity. ME are isotropic, stable transparent systems of with a droplets diameter>500 nm. Due to small droplets size, they may serve an excellent carrier for drugs having poor water solubility. Lornoxicam is derivative of allylamine, and is used orally in the treatment of hepatic failure, neutropenia. Methods: In the present study an attempt was made to increase solubility of Lornoxicam by the means of ME formulations. Oil, surfactant and co-surfactant were selected based on their solubility criteria. Total 5 formulations were developed using water titration method. Prepared formulations were evaluated on different parameters. Results: The percent transmission was found to be in the range of 98.48±0.15to 99.42±0.04. Refractive index for the micro emulsion formulations was found to be in the range of 1.3218±0.009 to 1.3720±0.021. Percent drug content was found to be in the range of 98.47±0.08 to 99.75±0.21. ME5 has shown faster drug release 91.2±0.06% in an in-vitro study of 4 hrs. Conclusion: Study concluded that the means of microemulsions formulations solubility of Lornoxicam can be enhanced. Peer Review History: Received: 2 October 2022; Revised: 11 November; Accepted: 20 December 2022, Available online: 15 January 2023 Academic Editor: Dr. Sally A. El-Zahaby , Pharos University in Alexandria, Egypt, sally.elzahaby@yahoo.com Reviewers: Dr. Bilge Ahsen KARA, Ankara Gazi Mustafa Kemal Hospital, Turkey, ahsndkyc@gmail.com Dr. George Zhu, Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com